Zonasi Daerah Rawan Longsor Menggunakan Analisis Sistem Informasi Geografis Berdasarkan Metode AHP Pada Daerah Gunung Kidul Yogyakarta - Muhammad Joko Umbaran Haris Bahrudin (Universitas Alma Ata, 2018)
Abstract Data from the Yogyakarta Regional National Survey and Mapping Coordinating Board (Bakosurtanal), disasters that often occur in Yogyakarta are landslides, droughts, tornadoes.In this study, the modeling of potential landslides in the Gunung Kidul area of Yogyakarta has been carried out using GIS analysis and scoring and weighting methods with reference to PU Candy No. 22 /PRT /M /2007 concerning the Guidelines for Landslide Disaster Prone Areas and the Analytical Hierarchy Process (AHP) method. The results were in the form of Three Zoning landslide prone areas, namely high potential found in three Hamlets namely Kacangan Hamlet Hargomulyo Village located at N 42º E, Kedok Ploso N 186º E Hamlet, and Kembang Village Nglegi Hamlet N 160º E based on vulnerability maps landslides processed based on Permen PU No. 22 / PRT / M / 2007. While the Medium Zone is located in Karangduwet Hamlet, Ngalang Village N 95º E. The low vulnerability zone is located in Duwet Hamlet, Ngalang Village N 4º E. Criteria in the study area include lithology: 0,250, slope: 0,053, groundwater condition 0,304, soil structure: 0,161 , land cover: 0.102 and relative reief: 0.131 all criteria determination is based on landscape hazard evaluation factor (LHEF) which is processed based on AHP method and map overlay technique.